Numerical Estimation of Some Properties of Magnesium Aluminum Silicate Glass Ceramic - Ibrahiem, A. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Magnesium aluminum silicate of glass ceramic having different amounts of magnesium fluoride in the range (0-13.2)%. Thermal expansion coefficient and micro hardness of the base glass and glass ceramic samples are seen to be interdependent but due to the multi – component system, the behaviour is seen to be somewhat complex, with an increase in Mg F2 content. The thermal expansion coefficient increase and micro harness decrease, numerical simulation of thermal expansion and hardness is useful in this study, L2 – regression is used to calculate the two parameters associated with each glass component, by comparing the measured parameters and the calculated parameters ,it is useful to use such a method to calculate the quantity of the component used in manufacturing the glass & class ceramic.